Differential water quality in confined and free-flowing water bodies, Lebanon - Korfali, Samira Ibrahim (2003)
Integrated management of water resources is a major critical issue to be addressed in combating water stress in developing countries, such as Lebanon. At present, surface water is not properly used in Lebanon. This emphasises the importance of assessing surface water quality as a projected means to increase water availability. This study involves two different water bodies, the freely flowing Nahr-Ibrahin River and the Qaraaoun Reservoir, an impoundment of the Litani River. Water samples were collected from 16 chosen sites of each water body at four different dates during the dry season. Measured water parameters were temperature, pH, conductivity, BOD, HCO3-, Ca2+, Mg2+, Cl-, SO42-, PO43-, NO3-, NH3, Fe, Mn, Zn, Pb, and Cd. Statistical analysis of the data revealed significant differences in water quality. The differences could be attributed to the fact that whereas the Qaraaoun reservoir is receiving domestic waste discharges that lead to an increase in the CO2 content and a pH decrease, the Nahr-Ibrahim River is influenced by agricultural runoffs and industrial discharges that increase the pH values. Consequently, the water metal speciation of the two water bodies was different. The study indicated that the differential quality of the two water bodies could be attributed to the nature of the water resources and exposure to contaminants. This is crucial in recommending intervention studies to protect quality and promote the role of surface water use, as an integrated component of water management in Lebanon.